2,3-Diphenyl-1,3-thiazolidin-4-one - Yennawar, Hemant P. (International Union of Crystallography, 2014)
The title compound, C(15)H(13)NOS, is a chiral molecule crystallized as a racemate, with two molecules in the asymmetric unit. In each of the molecules, the five-membered thiazine ring has an envelope conformation, with the S atom forming the flap. In one molecule, the angle between the two phenyl-ring planes is 82.77 (7)°, while in the other it is 89.12 (6)°. In the crystal, molecules are linked into chains along the b-axis direction by C—H⋯O hydrogen bonds.